Study on Shift Work Problems Among Security Team at University Tun Hussein Onn Malaysia, Parit Raja - MOHAMAD ZAMRI, MUHAMAD ADHAM ZUHRI; ISMAIL, SHAFAWI (Progress in Engineering Application and Technology, 2023)
Shift work, particularly that including night work has causes many health problems among workers in Malaysia. The aims of these study are to identify health problems and issues related to shift works and come out with new intervention plans to reduce the impacts to the shift workers. Data were analysed using SPSS software to get descriptive statistics on the demographic parameters of the respondents and to investigate the link between six factors affecting shift workers. The ANOVA findings revealed a statistically significant difference at p<0.05 for n= 50 to demographics of Position Categories and Education background, but no significant difference for Age Category and Years of Service in their judgements of shift work challenges at UTHM security team. Furthermore, Pearson Correlations analysis revealed a strong statistical correlation r >0.05, n= 50, p<0.05, between Behaviour Shift Workers, Workplace Accidents, Family and Social Life Problems, Health/Disease Problems, and Sleep/Wakeup Problems, but no statistical correlation between Organization/Department Roles and Responsibilities. Suitable interventions programs from the organization on shift schedule in according with ergonomic, health surveillance and social upkeep for shift workforces are vital precautionary and remedial measures. It allows employees to keep working without substantial health impairment